Analysis Of Factors Affecting Fiscal Stress In Local Goverments (Case Studies in Districts Kunci Bersama Areas for the Period of 2015 - 2019) - Neni - Nurhayati (Indonesian Journal Of Business And Economics, 2020)
ABSTRACTThis study aims at determining the effect of local revenue and capital expenditure on Fiscal Stress in the Kunci Bersama Area in 2015-2019. The population of this study is the district/city government in the Kunci Bersama Area. The entire population becomes a sample called the saturated sample (census). This study has 45 data observations derived from 9 districts/cities' financial statements for the 2015-2019 period. The data used in this study is secondary data in the form of a Budget Realization Report in the Kunci Bersama Areas for the 2015-2019 Period. The hypothesis testing tool in this study is the Eviews 9 software. From the test results, it is found that local revenue and capital expenditure affect fiscal stress. Local revenue has a negative effect on fiscal stress, while capital expenditure positively affects fiscal stress.